Józef Beck a Czechosłowacja w roku 1938. Czy wchodziła w grę alternatywna opcja polityki polskiej? - Kornat, Marek (1971– ) (Instytut Historii PAN, 2025)
This article examines the highly contentious topic of Polish diplomacy’s actions towards Czechoslovakia during the Sudeten crisis, which ultimately led to the resolutions reached at the Munich Conference, attended by the heads of government from the four powers. It also investigates the Polish ultimatum issued to the government in Prague, demanding the cession of Cieszyn Silesia. The author analyses the dilemmas faced by Minister Józef Beck and poses questions about whether a different political approach could have emerged in 1938, particularly regarding the appeasement policy of the Western powers.
p. 105-123
Summary in English.
Keywords: Beck, Józef, 1894-1944; Sudeten Crisis; 1938; Poland; Czechoslovakia; Europe - politics and government - 1918-1945; Munich Agreement (1938); Poland - foreign relations - Czechoslovakia - 1900-1945; Czechoslovakia - relations - Poland - 1900-1945; Poland - foreign - relations - 1918-1945